The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.3389/fonc.2021.709278
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Effectiveness of Adjuvant Treatment for Resected Hepatocellular Carcinoma: A Systematic Review and Network Meta-Analysis

Abstract: BackgroundIt is controversial whether adjuvant treatment could be recommended for hepatocellular carcinoma (HCC) after curative hepatectomy. Thus, we performed a network meta-analysis (NMA) to assess adjuvant treatment’s benefit and determine the optimal adjuvant regimen.MethodsWe systematically searched PubMed, Embase, and Cochrane Library for randomized controlled trials comparing adjuvant therapy versus no active treatment after curative hepatectomy among patients with HCC. Pooled data on recurrence and ove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 62 publications
0
16
0
Order By: Relevance
“…In the stratification analysis, young patients with early-stage HCC who received LT combined with chemotherapy had a superior survival (HR, 0.36; 95% CI: 0.19-0.66; P interaction=0.0004) compared with non-surgery patients. Previous studies have shown that after LT, adjuvant chemotherapy such as the FOLFOX regimen for HCC significantly prolongs patients' survival (34)(35)(36). However, few studies have focused on the association of other chemotherapy regimens and LT; hence, more randomized controlled clinical trials are needed for further validation.…”
Section: Discussionmentioning
confidence: 99%
“…In the stratification analysis, young patients with early-stage HCC who received LT combined with chemotherapy had a superior survival (HR, 0.36; 95% CI: 0.19-0.66; P interaction=0.0004) compared with non-surgery patients. Previous studies have shown that after LT, adjuvant chemotherapy such as the FOLFOX regimen for HCC significantly prolongs patients' survival (34)(35)(36). However, few studies have focused on the association of other chemotherapy regimens and LT; hence, more randomized controlled clinical trials are needed for further validation.…”
Section: Discussionmentioning
confidence: 99%
“…Although the prognosis varies among treated patients, the rate of tumor recurrence is generally high [ 86 ]. Adjuvant therapy decreases the risk of recurrence and provides survival benefits after surgical HCC resection [ 87 ].…”
Section: Clinical and Preclinical Applicationsmentioning
confidence: 99%
“…Moreover, the overall outcomes of these interventions are variable, and rendering the improvement of prognosis for these patients is a major challenge. 9 …”
Section: Introductionmentioning
confidence: 99%